Angina Pectoris - Piscione, Federico (IntechOpen, 2011)
Angina is the most common disorder affecting patients with ischemic heart disease. This book provides a thorough review of fundamental principles of diagnosis, pathophysiology and treatment of angina pectoris, representing an invaluable resource not only for cardiologists, but also for general practitioners and medical students.